(untitled) (Journal of the College of Languages (JCL), 2022)
The Beggar (1965) is a story of isolation and depression which is written by the Egyptian novelist Naguib Mahfouz who is considered the father of Arabic Literature in the modern era. Specifically, he refers in his great novel called The Beggar that the man unable to achieve psychological revival after Nasser’s revolution, the man sacrificed his own job and his family for a desire that increases his feelings of alienation and depression which leads him to an emotional outcry against the indifferent. The main aim of the study highlights the concept of existential dilemma as a philosophical problem and personality crisis by the protagonist of The Beggar novel, Omer Al-Hamzawi who had accepted the death instead of living in the real-life, as a result, was looking for the meaning of life, existence and evaded his truth through searching for a new value that renews the meaning of life that guided him to nothing to find himself living in a double personality and could not get rid of it ultimately.